2017
DOI: 10.4314/ahs.v17i2.33
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B<sub>6</sub> and homocysteine levels in carbamazepine treated epilepsy of Khyber Pakhtunkhwa

Abstract: Objectives: The study focused on the plasma levels of vitamin B 6 and homocysteine in different genotypes of MTHFR (C677T, A1298C) and GABRG2 (C588T, C315T) genes in carbamazepine resistant epilepsy in the population of Khyber Pakhtunkhwa. Methodology: Patients who were possible candidates for carbamazepine therapy were followed for six months for their seizure control. Plasma levels of vitamin B 6 and homocysteine were determined using immunoassay based techniques at baseline and after six months. MTHFR (C677… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…metabolic effect through deficiency of vitamin B6 that helps in synthesis of inhibitory neurotransmitters. More, in these resistant patients, we found that vitamin B6 level was deficient in heterozygous variants of MTHFR gene [14]. The relation to plasma levels is not so much string as the genotypes are associated with clinical outcomes.…”
Section: Discussionmentioning
confidence: 74%
“…metabolic effect through deficiency of vitamin B6 that helps in synthesis of inhibitory neurotransmitters. More, in these resistant patients, we found that vitamin B6 level was deficient in heterozygous variants of MTHFR gene [14]. The relation to plasma levels is not so much string as the genotypes are associated with clinical outcomes.…”
Section: Discussionmentioning
confidence: 74%
“…But we are of opinion that variants (677CT, 677TT and 1298 AC, 1298CC) of MTHFR gene may have association with poor seizure control during carbamazepine therapy in epileptic Pakhtun patients of KP due to indirect metabolic effect through deficiency of vitamin B6 that helps in synthesis of inhibitory neurotransmitters. More, in these resistant patients, we found that vitamin B6 level was deficient in heterozygous variants of MTHFR gene [ 14 ]. The relation to plasma levels is not so much string as the genotypes are associated with clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ]. So far relations have been reported with MTHFR (C677T and A1298C) genotypes polymorphism and elevated levels of homocysteine due to vitamin B6, B12 and folic acid deficiency [ 13 , 14 ]. More, we have recently observed that heterozygous variant (677CT and 1298 AC) of MTHFR gene frequently experienced low level of vitamin B6, which helps in synthesis of GABA, inhibitory neurotransmitters in carbamazepine treated patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed prolonged CBZ therapy reduces plasma B6 level significantly. 2,3 Vitamin B 6 plays an important role in treatment of epilepsy. Pyridoxal phosphate, active from of Vitamin B 6 is essential for formation of inhibitory neurotransmitter GABA.…”
Section: Introductionmentioning
confidence: 99%